Tuning the Surface Chemistry of MXene to Improve Energy Storage: Example of Nitrification by Salt Melt. Issue 2 (23rd November 2022) - Liu, Liyuan; Zschiesche, Hannes; Antonietti, Markus; Daffos, Barbara; Tarakina, Nadezda V.; Gibilaro, Mathieu; Chamelot, Pierre; Massot, Laurent; Duployer, Benjamin; Taberna, Pierre‐Louis; Simon, Patrice
Abstract: The unique properties of 2D MXenes, such as metal‐like electrical conductivity and versatile surface chemistry, make them appealing for various applications, including energy storage. While surface terminations of 2D MXene are expected to have a key influence on their electrochemical properties, the conventional HF‐etching method limits the surface functional groups to F, OH, and O. In this study, O‐free, Cl‐terminated MXenes (noted as Ti3 C2 Cl x ) are first synthesized by a molten salt (FeCl2 ) etching route. Then, a substitution of surface termination from Cl to N is performed via post‐thermal treatment of Ti3 C2 Cl x in Li3 N containing molten salt electrolytes. While the Cl‐terminated pristine material does not show electrochemical activity, the surface‐modified, N‐containing Ti3 C2 T x exhibits a unique capacitive‐like electrochemical signature in sulfuric acid aqueous electrolyte with rate performance—more than 300 F g −1 (84 mAh g −1 ) at 2 V s −1 . These results show that control of the MXene surface chemistry enables the preparation of high‐performance electrodes in a previously not accessed limit of energy storage. Abstract : Surface termination substitutions from Cl to N is performed via post thermal treatment of Ti3 C2 Cl x in Li3 N containing molten salt electrolyte. While the Cl‐terminated pristine material does not show electrochemical activity, the surface‐modified, N‐containing Ti3 C2 T x MXenes exhibit a unique electrochemical signature in sulfuric acid aqueous electrolyte with a high‐rate, capacitive‐like redox process within the full voltage window.